Politika sa mga Obra ng Pantas ng Pelikulang Pilipino: Ang mga Ideolohiyang Politikal sa mga Pelikula ni Ishmael Bernal (Politics in the Works of the Genius of Philippine Cinema: The Political Ideologies in the Films of Ishmael Bernal) - Liwanag, Lois Mauri Anne; Capague, Von Griel; Luglug, Marie Frances Therese (Social Sciences and Development Review, 2024)
The main purpose of this paper is to identify the political ideologies in five films of Ishmael Bernal: Manila by Night “City After Dark” (1980); Himala (1982); Broken Marriage (1983); Hinugot sa Langit (1985); and Pahiram ng Isang Umaga (1989). The basis of the selection of these films are the nominations and awards they received specifically from the Gawad Urian Awards which gave them either the Best Film of the Decade or the Best Picture award. As its hermeneutical lens, this paper utilized the two-dimensional ideological spectrum of the German theorist Hans Slomp, modified by F.P.A. Demeterio in his book titled Ang Mga Ideolohiyang Politikal ng Catholic Bishops’ Conference of the Philippines. This is based on the research of Felicilda and Demeterio (2019) where the said lens was used to determine the political ideologies in the five novels of the Rosales Saga by F. Sionil Jose. In order to accomplish the goal of this research, it has five substantive sections that each analyzes the following: 1) primary message and theme of the film; 2) its stand on status quo and change; 3) its esteem for the individual and state; and 4) its overall political ideology.